Towards an atlas of rare and threatened flora in the province of Cuenca (Spain): the case of "Erodium macrocalyx" (Geraniaceae) as a model species - García Cardo, Oscar; Martínez Labarga, Juan Manuel; Bartolomé Esteban, Carmen (Mediterranean Botany, 2018)
Not only the geography but other environmental features of Cuenca province (Spain) makes it rich in plant species of very different origins, some of which have been attributed to different categories of protection. The purpose of this study was to select species that might help understand migratory or speciation processes, perhaps due to their scarcity and their unique distribution, and irrespective of whether they are included in any normative framework or not. As such, here we present the method used to elaborate an atlas of the relatively rare and threatened flora in this province, using Erodium macrocalyx (G. López) López Udias, Fabregat & Mateo as a model species.